KESIAPAN GURU KELAS MELAKSANAKAN LAYANAN BIMBINGAN DAN KONSELING - Putri, Suci Mustika; Khairani, Khairani; Yusri, Yusri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2015)
Readiness is the condition of a person who makes him ready to respond in a certain way to the situation. This study aims to (1) describe the readiness of classroom teachers to carry out guidance and counseling services in primary schools throughout Padang viewed from the aspect of knowledge, (2) describe the readiness of class teachers to carry out guidance and counseling services in elementary schools throughout Padang City viewed from aspects skills, (3) describe the readiness of class teachers to carry out guidance and counseling services in primary schools throughout the city of Padang viewed from the aspect of attitude. This type of research is quantitative descriptive research. The population of the study came from elementary school (SD) teachers throughout the city of Padang totaling 429 teachers in grades 4, 5 and 6. Samples were taken using Cluster random sampling techniques, so that the number of samples was 37 teachers of grades 4, 5, and 6. The research was carried out by administering the questionnaire instrument. Data is analyzed by percentage analysis. The research findings show the results of the readiness of class teachers to carry out guidance and counseling services in elementary schools throughout the city of Padang in the good category. Keywords: Teacher readiness, Guidance and Counseling in Elementary School